Significance of Tulsi plant in a Koli household - Mumbai Archive Project Team (Jio Institute, 2024)
In Koli tradition, the Tulsi plant holds great reverence and is situated in the courtyard of the home. Every evening, Meena Nakhva offers prayers at the Tulsi shrine, lighting incense sticks and a diya (oil lamp).